2020
DOI: 10.5812/asjsm.100261
|View full text |Cite
|
Sign up to set email alerts
|

Physical Health Status of Emergency Care Providers in South Africa

Abstract: Background: Emergency care providers (ECPs) have a physically, mentally, and emotionally demanding profession. Therefore, they are predisposed to cardiovascular and other non-communicable disease risk factors. Objectives: The objective of the study was to determine the physical health status of ECPs in the North West province of South Africa through a selected anthropometric and other health parameter test battery. Methods: Ninety-one ECPs (64 males, 27 females) took part in the study voluntarily for health sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Studies investigating the relationship between physical fitness components of ECPs and their occupational tasks in South Africa and globally are uninitiated. Only a few studies have investigated the fitness levels and physical health measures among ECPs (5,6), despite the literature detailing the demonstration of the physical demands in the profession. For example, Russo et al (7) examined the impact of physical fitness on the quality of external chest compressions during CPR and found that rescuers of superior physical fitness were able to sustain high quality chest compressions and lower rescuer fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the relationship between physical fitness components of ECPs and their occupational tasks in South Africa and globally are uninitiated. Only a few studies have investigated the fitness levels and physical health measures among ECPs (5,6), despite the literature detailing the demonstration of the physical demands in the profession. For example, Russo et al (7) examined the impact of physical fitness on the quality of external chest compressions during CPR and found that rescuers of superior physical fitness were able to sustain high quality chest compressions and lower rescuer fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…These include increases in the risk of injury and illness among emergency care providers acquired during the performance of their operational duties (11). Work-related injuries and illnesses are problematic in that they have the potential to negatively affect, not only the emergency care provider, but also their colleagues and members of the public they are there to assist (14). By extrapolation, for a BEMC student to operate effectively and safely in the emergency medical care and medical rescue environments, they too would need to possess certain minimum levels of physical preparedness (3).…”
Section: Introductionmentioning
confidence: 99%